Semi-automatic 3D topological network extraction for indoor navigation - Claridades, Alexis Richard C.
The demand for 3D spatial data is increasing with the growing complexity of indoor spaces. As human beings spend more time indoors, more focus is given to indoor location-based applications and services. Topological networks in three dimensions are used for various spatial applications that involve navigation in the indoor environment such as emergency evacuation, indoor positioning, accessibility studies, and visualization. Manual methods of generating indoor network data are impractical, laborious to perform, and are prone to errors, but current methods in automating the process need expensive sensors or datasets that are difficult and expensive to obtain and process. In this research, a methodology for semi-automatically generating a 3D indoor topological model capable of representing adjacency, connectivity, and accessibility of indoor spaces is proposed. Among numerous existing standards for the storage and exchange of 3D spatial data, IndoorGML was selected to be used for this research, as the standard has been crafted specifically for indoor navigation. The concept of Shooting Point is defined to accommodate the usage of omnidirectional images in generating IndoorGML data. Omnidirectional images were captured at selected Shooting Points in the building study area using a fisheye camera lens and rotator. Spaces in the interior were detected from the images using image processing techniques implemented in Python script. Relative positions of spaces obtained from CAD drawings were used to generate 3D networks in the form of node-relation graphs representing adjacency, connectivity, and accessibility of indoor spaces in the study area. Subspacing is performed to more accurately depict large indoor spaces and reflect actual pedestrian movement. Since the images can provide very realistic visualization, the topological relationships were used to link the images to produce a visualization in the form of a virtual indoor tour.